Disabled People’s Experiences in Rehabilitation: A Perspective of Gender and Age - Sólrún Óladóttir; Marte Feiring; Guðmundur Kristján Óskarsson; Snæfríður Þóra Egilson (Scandinavian Journal of Disability Research)
Framed within a critical realist perspective, this mixed-methods study examined rehabilitation practices in Iceland as experienced by disabled people. Altogether, 499 people were surveyed at the end of their rehabilitation period. Subsequently, interviews were conducted with 10 disabled people who had received rehabilitation services to elaborate on the survey results and provide insight into their lives after discharge from the rehabilitation unit. In the survey, women more often reported that the services and family involvement during rehabilitation were not in line with their needs and preferences. In the interviews men were more positive towards the rehabilitation program and described more respectful interactions with professionals. However, overall, participants felt that the gains they had made in rehabilitation had not translated well into their daily lives. The study underscores the importance of gender awareness in rehabilitation practices, and the importance of gender-sensitive, person-centered services that acknowledge each individual’s unique needs and circumstances.